Business financing for small and medium enterprise (SMEs): How to strike? - Mohd Harif, Mohd Amy Azhar; Md Zali, Siti Khadijah (2011)
Small and medium enterprises (SMEs) constitute an important part of the business system in Malaysia. Although their role in the Malaysian national economy has been one of distinction and contribution, but SMEs possess a lack of financial to expand their business. Thus, the purpose of this research is to investigate the factors considered by banks in providing the financing to Small and Medium Enterprise (SMEs) in Malaysia. This study is focused on question: “Business financing for Small and Medium Enterprise (SMEs): How to strike?” To answer the research problem, this research employs the convergent interview with the commercial banks including SME Bank around Malaysia. This research have been used a cross case analysis technique to analyzed data. From this analysis, the result suggested that have 15 factors classified as a success factors in getting the business financing for SMEs.